Pengaruh Mendengarkan Lagu Berbahasa Inggris Dalam Meningkatkan Kemampuan Bahasa Inggris Mahasiswa Pendidikan Bahasa Inggris - Utomo, Slamet (WASIS : Jurnal Ilmiah Pendidikan, 2025)
In addition to formal and non-formal education, English language skills in this modern era can also be improved in various ways, both structured and independent. One way that can be done to improve English skills independently is by listening to English songs. This study aims to determine whether there is an effect of listening to English songs on improving English language skills. The type of research used in this study is quantitative. The study was conducted on English Education students at Muria Kudus University. Based on the results of the study obtained from 83 research respondents who attended, it can be seen that listening to English songs can improve English listening, pronunciation, reading, understanding and writing skills